2005
DOI: 10.1128/aem.71.2.1093-1096.2005
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of glpC , an Organic Solvent Tolerance-Related Gene in Escherichia coli , Using Gene Expression Profiles from DNA Microarrays

Abstract: Gene expression profiles were collected from Escherichia coli strains (OST3410, TK33, and TK31) before and after exposure to organic solvents, and the six genes that showed higher gene expression were selected. Among these genes, glpC encoding the anaerobic glycerol-3-phosphate dehydrogenase subunit C remarkably increased the organic solvent tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…In this study, the effects of inactivation of the glpC gene in P. vulgaris yielded similar results to those obtained by Shimizu (2005). The sensitivity of the mutant strain to n-hexane stress was unchanged compared to that of the wild-type strain.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this study, the effects of inactivation of the glpC gene in P. vulgaris yielded similar results to those obtained by Shimizu (2005). The sensitivity of the mutant strain to n-hexane stress was unchanged compared to that of the wild-type strain.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, the glpC gene was identified as the insertion site in the obtained biofilm defective strain. In E. coli, glpC has been demonstrated to play an important role in increasing the organic solvent tolerance, through analysis of gene expression profiles before and after exposure to organic solvents (Shimizu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2) and also identified an isopropylmalate dehydrogenase (CAC0970) adjacent to aconitase (CAC0971) to be part of the specific butanol-stress response. Glycerol metabolism genes have been implicated with hexane tolerance in the solvent-tolerant E. coli strain OST3410 which expresses the glycerol metabolism genes glpB, glpC (both are glycerol-3-phosphate dehydrogenase subunits), glpF (glycerol uptake facilitator), and glpQ (glycerophosphoryl diester phophodiesterase) higher than the parent strain JA300, and also upregulated expression of these genes in OST3410 following hexane stress (Hayashi et al, 2003), while higher expression of glpC has also been observed in other solvent-tolerant E. coli strains following treatment with xylene and cyclohexane (Shimizu et al, 2005). We observed differential upregulation of a glycerol uptake facilitator (glpF, CAC1319) and a glycerol-3-phosphate dehydrogenase (glpA, CAC1322) following butanol stress in C. acetobutylicum, suggesting a conserved mechanism of solvent tolerance.…”
Section: Genes Specific To the Butanol-stress Responsementioning
confidence: 96%
“…Many organic-solvent-tolerant bacteria have been isolated, and the elucidation of their tolerance mechanisms is in progress (10,(15)(16)(17). However, there is insufficient knowledge concerning organic-solvent-tolerant eukaryotic cells (26).…”
Section: Fig 1 Growth Curves Ofmentioning
confidence: 99%